Plastic Waste Management through Pyrolysis in the Seribu Islands: Energy Efficiency and Fuel Oil Production Analysis - Raharjo, Bambang; Winanda, Aryan; Triwinanto, Puguh; Firdhaus, Taufan; Nursiwan; Prawoto; Maulana, Eka (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
Plastic waste in the Seribu Islands has become a significant issue threatening marine and coastal ecosystems. This study analyzes the conversion of plastic waste into diesel fuel through pyrolysis, employing three scenarios of plastic mixture ratios: LDPE and PP, PET, PS, and HDPE. With operating temperatures of 400 °C, 480 °C, and 550 °C, the research evaluates energy efficiency, diesel output, and return on investment (ROI). Results indicate that a mixture of 50% LDPE and PP, 15% PET, 10% PS, and 25% HDPE at 550 °C produces the highest diesel yield of 0.805 tons per 1,000 kg of plastic. The annual ROI is recorded at 0.26%, highlighting the project's potential to support environmental conservation while providing economic benefits